Réfléchir sur le féminisme du troisième millénaire - Dumont, Micheline (Dialogues sur la troisième vague féministe, 2005)
"Dialogues sur la troisième vague féministe rassemble des voix qui, chacune à sa manière, propose des pistes de réflexion quant à la nature des changements qui affectent le féminisme québécois. Ces dialogues explorent des thématiques liées au pouvoir, à la sexualité et à l'image du corps, liées à la mondialisation, aux conflits générationnels, au backlash, et à la relation entre la théorie, la pratique et la culture populaire."--Couverture.
Keywords: 1900-1999; 1990-1999; amériques; corps; cours; discipline; fem1000; histoire et politique; mouvements féministes; premier cycle; périodes historiques; québec; régions géographiques; sexualité; thématiques

Black sexual politics: African Americans, gender, and the new racism - Hill Collins, Patricia (Routledge, 2005)
To a large extent, scholarship on black politics often focuses primarily on institutions, rule of law, processes, political actors, and citizens but with very little attention to issues of gender and sexuality. In contrast, the principal aim of this book is to explore what the author sees as the inextricable links between racism and gender. The basic thesis of this well-written, important, and provocative book is that the fight against racism, especially the “new racism,” can never be won without first challenging sexism, which simultaneously oppresses African-American men and women.
Keywords: afro-féminisme; amériques; approches et analyses; corps; cours; discipline; féminisme afroaméricain; féminismes noirs; intersectionnalité; premier cycle; racisme; ressource en ligne; régions géographiques; science politique; science politique et droit; sciences humaines; sex2283; sexisme; sexualité; sociologie; systèmes d'oppressions; thématiques; théorie critique de la race; violences; états-unis

Attitudes Toward Victims of Rape: Effects of Gender, Race, Religion, and Social Class - Nagel, Barbara; Matsuo, Hisako; McIntyre, Kevin P.; Morrison, Nancy (Journal of Interpersonal Violence, 2005)
Although previous literature focusing on perceptions of victims of rape has examined how gender, race, and culture influence the attitudes one holds toward victims, these studies have yielded mixed results. This study compared perceptions of victims of rape across a wide range of ages, educational backgrounds, religions, and income levels, while focusing on gender and racial differences. Results indicate (N = 220) that victims of rape are generally viewed more sympathetically by females than by males and by Whites than by African Americans. However, the effect of race disappears when socioeconomic variables are controlled, suggesting a more complex relationship. Also, a hierarchical regression indicates that age, sex, education, and income are significant predictors of attitudes toward victims. This study builds on existing research that examines such attitudes from a cultural perspective and extends this literature by examining the interactive effects of several demographic variables within a community sample.
Keywords: 2000 à aujourd'hui; 2000-2009; amériques; anthropologie; approches et analyses; corps; cours; discipline; intersectionnalité; premier cycle; périodes historiques; ressource en ligne; régions géographiques; sciences humaines; sex2283; thématiques; viol; violences; états-unis

Domestic violence at the intersections of race, class, and gender: challenges and contributions to understanding violence against marginalized women in diverse communities - Sokoloff, Natalie J; Dupont, Ida (Violence against women, 2005)
This article provides a comprehensive review of the emerging domestic violence literature using a race, class, gender, sexual orientation intersectional analysis and structural framework fostered by women of color and their allies to understand the experiences and contexts of domestic violence for marginalized women in U.S. society. The first half of the article lays out a series of challenges that an intersectional analysis grounded in a structural framework provides for understanding the role of culture in domestic violence. The second half of the article points to major contributions of such an approach to feminist methods and practices in working with battered women on the margins of society.
Keywords: 2000 à aujourd'hui; 2000-2009; afro-féminisme; amériques; approches et analyses; care; corps; cours; criminologie; discipline; féminisme afroaméricain; intersectionnalité; premier cycle; périodes historiques; ressource en ligne; régions géographiques; sciences humaines; sex2283; sociologie; thématiques; violences; états-unis